Employee Motivation Strategies To Improve Performance In The Sundanese Cultural Background Business Organization - Bima Hermastho (CV. Publikasi Indonesia, 2023)
Employee motivation strategies to improve performance in the Sundanese cultural background business organization, there are results of research conducted in the Sundanese cultural environment. This study seeks to examine factors that influence work motivation in an effort to improve performance both individually and organizations in employees in business organizations with a background in the Sundanese culture. This research is literature research, where the data collection comes from various journals and books analyzed according to existing problems. The result showed factors of motivation consisting of salary and social security, type of work, hope for a career, working complete, the role of managers, work environment, employee competence, and company policies have a positive and significant influence on the performance of employees at companies Sundanese cultural background. And there are several ways or strategies for a company manager in an effort to improve the work motivation of its employees so that the company's performance can be achieved according to expectations